Novel Immunotherapy Options for Extranodal NK/T-Cell Lymphoma - Hu, Boyu; Oki, Yasuhiro (Frontiers in Oncology, 2018)
Extranodal NK/T-cell lymphoma (ENKTCL) is a highly aggressive mature NK/T-cell neoplasm marked by NK cell phenotypic expression of CD3ε and CD56. While the disease is reported worldwide, there is a significant geographic variation with its highest incidence in East Asian countries possibly related to the frequent early childhood exposure of Epstein-Barr virus (EBV) and specific ethnic-genetical background, which contributes to the tumorigenesis. Historically, anthracycline-based chemotherapy such as CHOP (cyclophosphamide, adriamycin, vincristine and prednisone) was used, but resulted in poor outcomes. This is due in part to intrinsic ENKTCL resistance to anthracycline caused by high expression levels of P-glycoprotein. The recent application of combined modality therapy with concurrent or sequential radiation therapy for early stage disease, along with non-anthracycline based chemotherapy regimens consisting of drugs independent of P-glycoprotein have significantly improved clinical outcomes. Particularly, this neoplasm shows high sensitivity to L-asparaginase as NK-cells lack asparagine synthase activity. Even still, outcomes of patients with advanced stage disease or those with relapsed/recurrent disease are dismal with overall survival of generally a few months. Thus, novel therapies are needed for this population. Clinical activity of targeted antibodies along with antibody-drug conjugates such as daratumumab (naked anti-CD38 antibody) and brentuximab vedotin (anti-CD30 antibody conjugated with auristatin E) have been reported. Further promising data has been shown with checkpoint inhibitors as high levels of PD-L1 expression are observed in ENKTCL due to EBV-driven overexpression of the latent membrane proteins (LMP1 and LMP2) with activation of the NF-κB/MAPK pathways. Initial case series with PD-1 inhibitors showed an overall response rate of 100% in seven relapsed patients including five with a complete response (CR). Furthermore, cellular immunotherapy with engineered cytotoxic T lymphocytes (CTLs) targeted against LMP1 and LMP2 have shown encouraging results with durable CRs as either maintenance therapy after initial induction chemotherapy or in the relapsed/refractory setting. In this paper, we review this exciting field of novel immunotherapy options against ENKTCL that hopefully will change the treatment paradigm in this deadly disease.